A new therapeutic effect of fenofibrate in Duchenne muscular dystrophy: The promotion of myostatin degradation. (23rd December 2021) - Sun, Zeren; Xu, Dengqiu; Zhao, Lei; Li, Xihua; Li, Sijia; Huang, Xiaofei; Li, Chunjie; Sun, Lixin; Liu, Bing; Jiang, Zhenzhou; Zhang, Luyong
Abstract : Background and Purpose: Duchenne muscular dystrophy (DMD) is a degenerative muscle disease with no effective drug treatment. This study investigated the positive effects of fenofibrate on dystrophic muscles. Experimental Approach: Myostatin expression in serum and muscle tissue from patients with Duchenne muscular dystrophy and mdx mice were tested. Primary myoblasts isolated from mdx mice were challenged with an inflammatory stimulus and treated with fenofibrate. In animal experiments, 6‐week‐old male mdx mice were treated with fenofibrate (100 mg kg ‐1 ) administered orally once per day for 6 weeks. Effects of fenofibrate were evaluated by tests of muscle function plus histology and biochemical analyses of serum. Expression of myostatin, MuRF1, and atrogin‐1 in skeletal muscle was evaluated by western blotting and real‐time PCR. Total and oxidative myosin heavy chain (MHC) were assessed via immunofluorescence. Key Results: Expression of myostatin protein was increased in dystrophic muscle of patients with Duchenne muscular dystrophy and mdx mice. Fenofibrate enhanced myofibre differentiation by down‐regulating the expression of myostatin protein but not mRNA in primary myoblasts of mdx mice. Fenofibrate significantly improved muscle function while ameliorating muscle damage in mdx mice. These benefits were accompanied by an anti‐inflammatory effect. Fenofibrate treatment returned myofibre function by inhibiting the expressions of myostatin, MuRF1, and atrogin‐1 protein in the gastrocnemius muscle and diaphragm, while leaving the mRNA level of myostatin unaffected. Conclusions and Implications: Fenofibrate substantially slows muscle dystrophy by promoting the degradation of myostatin protein, which may indicate a new therapeutic focus for patients with Duchenne muscular dystrophy. Abstract :